Monitoring of solid waste polygons and the buffer zone based on remote sensing data (Journal of Geography and Environmental Management, 2017)
Implementation of the Concept of transition of the Republic of Kazakhstan to the "green economy" [1] includes measures to modernize the municipal solid waste management system. Specificity of the Republic geographical position, peculiarities of civil and industrial objects placement makes it difficult to manage the solid waste system without the use of remote sensing and the development of the scientific basis for Space Research is actual. The technology of monitoring has been developed for legal polygons under the project "Create geographic information system of space monitoring on the basis of advanced thematic processing of satellite information technologies of solid waste polygons, the Republican budget program 076 of "NCSRT". Technology is based on the data of remote sensing (RS) and presumes the calculate of following parameters changes: area of the solid waste polygon and its compliance with the legal boundaries of the polygons regulated by permits, waste areas within selected polygon, identification of changes in the buffer zone of the polygons. To test this technology six official solid waste polygons differing by according to the type, area and landscape conditions of accommodation were selected.
Keywords: Solid waste polygons; monitoring; remote sensing data